Group B streptococcus-induced nitric oxide production in murine macrophages is CR3 (CD11b/CD18) dependent. - Goodrum, K J (1994)
Nitric oxide (NO) is produced by murine macrophages in response to cytokines and/or gram-negative bacterial lipopolysaccharide. NO induction by gram-positive bacteria such as group B streptococci (GBS), the major etiologic agents of neonatal pneumonia and meningitis, has received little study. GBS as well as two other gram-positive bacterial species, Staphylococcus aureus and Staphylococcus epidermidis, were found to stimulate NO production in thioglycolate-elicited murine macrophages and in the mouse macrophage cell line J774A.1 in the presence of gamma interferon. Serotype Ia and III GBS were both stimulatory, as were asialo- and type antigen-deficient mutant strains of type III GBS. NO production was dose dependent, inhibitable by L-arginine analogs, and unaffected by polymyxin B. Since phagocytosis by murine and human phagocytes of GBS is dependent on complement receptor type 3 (CR3), the role of CR3 in the NO response to GBS was tested in the CR3-deficient myelomonocytic cell line WEHI-3. GBS did not induce NO, whereas S. aureus or lipopolysaccharide did induce NO in WEHI-3 cells. S. epidermidis, whose nonopsonic phagocytosis is also CR3 dependent, failed to induce NO in WEHI-3 cells. Monoclonal anti-CR3 (anti-CD11b or anti-CD18) in the presence of interferon also induced NO production in thioglycolate-elicited macrophages and in J774A.1 cells but not in WEHI-3 cells. This evidence suggests that ligated CR3 and gamma interferon act synergistically to induce NO production and that CR3 mediates the GBS-induced signal for NO production in interferon-treated macrophages.